Exploring the Dynamics of Pay Later in E-Commerce: Trust, Security, Satisfaction, and Continuance Intent - Pribadi, Amanda; Kurnia, Pepey Riawati; Sitio, Rike Penta (Universitas Jakarta Internasional, 2023)
The ever-evolving landscape of the financial technology (FinTech) sector has witnessed a surge in the popularity of non-cash transactions on e-commerce platforms. Among these, the Pay Later option has gained considerable prominence as it allows users to defer payments, akin to traditional credit cards. This research delves into the crucial factors influencing users’ intention to continue using the Pay Later feature on e-commerce platforms, with a particular focus on the role of user satisfaction. We conducted an online survey using Google Forms to collect empirical data, targeting Pay Later users on e-commerce apps within the Jabodetabek region. Our study comprised a purposive sample of 401 respondents. The data was subjected to advanced statistical analysis, specifically variance-based structural equations modeling (SEM) employing the partial least squares (PLS) path modeling approach facilitated by SMARTPLS 3.0. Our findings indicate that user perception of security, trust, and user interface directly impacts their intention to continue using Pay Later. However, perceived enjoyment and perceived usefulness did not exhibit a direct correlation with continuance intention. Notably, user satisfaction emerges as a crucial mediator in the relationship between perceived security, trust, perceived usefulness, perceived enjoyment, and user interface on the one hand and users’ intention to continue utilizing Pay Later on the other. The implications of this study extend to stakeholders in the e-commerce industry, offering valuable insights that can be harnessed to enhance customer continuance intention and foster the widespread adoption of the Pay Later system within e-commerce platforms.